TINDAKAN MAIN HAKIM SENDIRI DI TANJUNG UNGGAT KOTA TANJUNGPINANG - Yusnidar Agusti; Siti Arieta; Rahma Syafitri (JURNAL SOSIO-KOMUNIKA, 2023)
Tanjung Unggat Sub-District is an area that is already classified as urban as the characteristics of urban areas with crime or crime. The act of taking the law into their own hands that took place in the Tanjung Unggat sub-district was an unnatural thing for the community to do. These beatings or beatings often occurred due to the emotions of the masses that could not be controlled. The purpose of this study is to find out the social construction that occurs in the Tanjung Unggat Village community towards vigilante acts. This study used qualitative methods and descriptive types, data collection was carried out using observation methods, interviews using interview guides and interview guides. In determining the informants the researcher used a purposive sampling technique by first determining the criteria for the informants, the informants that the researchers obtained totaled 8 informants. Data analysis in this study used data reduction, data presentation, conclusions and verification. As for the results in this study, there is social construction that occurs in the Tanjung Unggat Village community. this is a social construction made by society. Objective, namely the justification for vigilante actions, Society as an Objective Reality is created because there are individuals who externalize themselves or reveal their subjectivity through a series of activities that are carried out continuously. Internalization is the community's decision to take the law into their own hands. The people who live in the Tanjung Unggat Village are on average migrants. The large number of migrants shows increased mobility of the population and causes disharmony. Because of this, harmony between migrants and native residents of the Tanjung Unggat Village is urgently needed. In social life, harmony is an important element that must be maintained for the continuity and harmony of community life. With harmony there will be no vigilante acts and other problems